Problematika Implementasi Kurikulum Merdeka Pada Mata Pelajaran PAI Kelas 11 di SMA N 1 Bangsri - Diah, Silfiani; Andriyani, Santi (Indonesia, 2024)
The independent curriculum, announced by the Indonesian Ministry of Education and Culture Nadiem Anwar Makarim, is a new basic concept in the world of education. Islamic religious education directs students' physical and spiritual aspects based on religious standards. This research was conducted on Tuesday, January 9 2024 and Wednesday, January 19 2024 at SMA N 1 Bangsri. The aim of carrying out the research is to study problems related to the application of the independent curriculum in the class 11 PAI study field at the school. The subjects in the research were the head of the curriculum, grade 11 PAI teachers and grade 11 students. This study used qualitative methodology, which means collecting data from observations, interviews and documentation. Data collection techniques using primary data sources. Data analysis techniques, including collection, condensation, data display and verification. The results of the research that has been carried out state that the independent curriculum in class 11 PAI at SMA N 1 Bangsri has been implemented well. Outside of class, students are asked to carry out the Project for Strengthening the Pancasila Student Profile (P5). There are several problems related to the application of the independent curriculum in PAI subjects, such as lack of training for teachers, difficulty in implementing differentiated learning, and a lack of learning support facilities, such as slow internet speed. Resolving related problems can be addressed through meetings between teachers, condensing material and sharing between teachers.